2016
DOI: 10.4103/0972-0707.178686
|View full text |Cite
|
Sign up to set email alerts
|

Apical extrusion of debris by supplementary files used for retreatment: An ex vivo comparative study

Abstract: Aim:This study evaluated whether using supplementary files for removing root canal filling residues after ProTaper Universal Retreatment files (RFs) increased the debris extrusion apically.Materials and Methods:Eighty mandibular premolars with single root and canal were instrumented with ProTaper Universal rotary system (SX-F3) and obturated. The samples were divided randomly into four groups (n = 20). Group 1 served as a control; only ProTaper Universal RFs D1–D3 were used, and the extruded debris was weighed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…The HF were associated with higher amount of debris extrusion apically in this study, and this is in agreement with the existing literature. 8,11,12,[21][22][23][24] Our results showed that rotary files used in crown-down fashion extruded more debris than the SAF system. This may be detrimental to the underlying stem cells and lead to alterations in the dental germ, such as hypoplasia, morphological alteration on the dental crown, or total arrest of radicular formation.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The HF were associated with higher amount of debris extrusion apically in this study, and this is in agreement with the existing literature. 8,11,12,[21][22][23][24] Our results showed that rotary files used in crown-down fashion extruded more debris than the SAF system. This may be detrimental to the underlying stem cells and lead to alterations in the dental germ, such as hypoplasia, morphological alteration on the dental crown, or total arrest of radicular formation.…”
Section: Discussionmentioning
confidence: 91%
“…11,14,15 Many studies have been carried out and reported on the amount of apically extruded debris during root canal preparation using these newer instruments in permanent teeth. [1][2][3][4][5][11][12][13][16][17][18] The SAF reportedly is associated with less debris extrusion in studies reported on permanent teeth. 11,12 To the best of our knowledge , debris extrusion after instrumenting primary teeth using the aforementioned methods is yet to be reported.…”
Section: Jcdpmentioning
confidence: 99%
See 3 more Smart Citations